Avaliação de parâmetros fisiológicos e hemoparasitólogicos de Columbina talpacoti (Aves: Columbiformes): um estudo comparativo nos ambientes urbano e natural - Rodrigues, Regiane da Silva (2017)
Urbanization creates strong pressures on natural populations. Both richness and abundance of more susceptible species diminish due to urbanization, while generalized and / or opportunistic species tend to become more common, leading to a process known as biotic homogenization. Another important contribution of Urbanization is represented by the increasing rates in parasite transmission, mainly among birds. In this sense, the main purpose of this study was to evaluate how individuals of Columbina talpacoti respond in different special gradients: natural and urbanized environments. Three indices were analyzed: hematological, parasitological (avian malaria prevalence and parasitemia) and body condition. The study was carried out in the city of Uberlândia (MG). There were 4 collection points within the city and 7 collection points in the Clube de Caça e Pesca Itororó de Uberlândia. Captures were carried out from March 2016 to October 2016, by using mist nets, and collecting a blood sample and morphometric measurements from each individual. Blood collection was done through a venipuncture, getting a drop of non-heparinized blood to make three blood smears. Two blood drops were conditioned in absolute alcohol in microtubes for later DNA extraction and PCR procedures. Data analysis was performed using Mann-Whitney test to verify the existence of significant differences between the patterns analyzed between urban and natural areas. The data was submitted to both Pearson and Spearmann correlation test to check for possible correlation among the variables. Only one hematological index (heterophilic / lymphocyte ratio), which indicates stress, was higher for the urban than natural area (t = 3.673, p <0.05). The other indices were not statistically significant. There were also no significant differences between sex identities as well. Only the H/L index was positively related to the total leukocytes (rs = 0.394, p <0.05), shown by the correlation tests. These results indicate that animals are more stressed in the urban environment. Having high food availability coupled with a phenotypic plasticity of individuals, body condition did not change in any of the areas. In addition, since the infections evaluated are in the chronic stage, the symptoms of the disease are mild and almost non-existent.